Correlation between contractile properties of quadriceps muscle and functional performance in runners with patellofemoral pain syndrome - Elmahdy, Menan A; Ayad, Khaled; Metwally Abdelrahman, Amira; Shawki Abdelsalam, Mohammed (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
Background: Long distance runners commonly complain from patellofemoral pain syndrome (PFPS) that limits their performance and return to sport. Abnormal neuromuscular control of the quadriceps has been demonstrated to cause patellar mal-tracking and hence PFPS. Changes in muscle morphology and neural activity have a role in neuromuscular changes, a key contributor to either primary or secondary injuries. Poor landing mechanics, impaired postural control, as well as changed peripheral muscle activation are all clinical manifestations of neuromuscular control deficiencies caused by central nervous system defects that have a deleterious effect on the contractile characteristics of skeletal muscle. Objectives: The purpose of this study was to investigate the correlation between contractile properties of quadriceps muscle and functional performance in long distance runners with PFPS. Study design: Cross-sectional study. Methods: Thirty runners were recruited form multiple Egyptian clubs. Tensiomyography (TMG) Parameters were assessed regarding Contraction time (Tc), Maximal displacement (Dm), Sustain time (Ts), Relaxion time (Tr) and Delay time (Td) in Rectus femoris (RF), Vastus medialis (VM) and Vastus lateralis (VL) separately and correlated with functional performance; number of repetitions in 30 seconds for anteromedial lunge test, balance and reach test and step-down test. Outcome measures: Functional performance was measured using functional performance tests; anteromedial lunge test, balance and reach test and step-down test. Results: It was found that VM Tc, VL Dm, were moderately positively correlated with anteromedial lunge (r = 0.583, 0.404, p<0.05) respectively. In contrast, RF Tr was negatively correlated with anteromedial lunge (-0.364, p<0.05); VM Ts,Tr,Dm; VL Td were moderately negatively correlated with balance and reach (r = --0.577, -0.388, 0.655 and -0.385, respectively, p<0.05). In contrast, VL Tc was moderately positively correlated with step-down (r = 0.424, p = 0.019). Conclusion: All contractile properties of quadriceps muscle are significantly correlated with functional performance in long distance runners with PFPS. Future studies should address these properties, using proper rehabilitation strategies, to improve performance of runners with PFPS.